Isolation and Characterization of 11 New Microsatellite Loci in Erigeron breviscapus (Asteraceae), an Important Chinese Traditional Herb - Li, Xiang (Molecular Diversity Preservation International (MDPI), 2011)
Erigeron breviscapus (Vant.) Hand.-Mazz. (Asteraceae) is a species endemic to southwestern China and an important traditional Chinese herb for cardiovascular and cerebral vessel diseases. Applying a modified biotin-streptavidin capture method, 11 microsatellite loci were discovered. Polymorphism of each locus was assessed in 24 individuals collected from five wild populations. The number of alleles per locus ranged from 2 to 7, with an average of 4.273. The observed (HO) and expected (HE) heterozygosities varied from 0.250 to 0.958 and from 0.337 to 0.786, respectively. Over half of these loci were successfully amplified in two congeneric species. The developed microsatellite markers will be useful for future population genetics and conservation studies, as well as accurate identification of different varieties.